The reality of applying job circulation in the General Institute (public) administration in Riyadh city - al - Saab, Ishtayq bint Abdullah bin Ali (Journal of Economic, Administrative and Legal Sciences, 2018)
The study aimed to identify the degree of applying job circulation to the Institute of public administration in Riyadh city، to determine the positive aspects of job circulation in the Institute of Public Administration in Riyadh and to reveal the challenges that may limit the effectiveness of applying job circulation in the Institute of Public Administration in Riyadh from the point of view of the institute employees. The researcher used the descriptive approach. The study population consisted of the administrative and teaching staff working in the Institute. The number of the study population was 799، 207 out of which are valid and subjected to analysis. The researcher used the questionnaire as a tool to collect data. The study found the following results: The results showed that the study participants agreed to a fair degree on the reality of applying job circulation in the Institute of Public Administration in Riyadh، this average amounted to (2.78). The results of the study showed that the study population significantly agreed on the positive aspects of job circulation if applied on the institute of public administration in Riyadh، with general approval of (3.41). The most important of these positive aspects was the opportunity to gain new experiences and contribute to job circulation development. The results showed that the study participants agreed to a great extent on the challenges that limit the effectiveness of applying the job circulation to the employees of the Institute of Public Administration in Riyadh. The general average was 3.41. The most prominent of those were the lack of both material and moral incentives as well as the workers’ rejection to career circulation.